THE GENERATIVE REPRODUCTIVE CHARACTERISTICS OF RED DRAGON FRUIT (Hylocereus.polyrhizus (Web.) Britton & Rose, CACTACEAE) - Kriswiyanti, Eniek (Jurnal Biologi Udayana, 2013)
This study aimed to investigate the generative reproductive characteristics of red dragon fruit ( Hylocereus polyrhizus (Web.) Britton & Rose), that is the characteristics and the development of male and female reproductive system and the embryo. The flowering morphology was observed through the gametogenesis process and the process of embryogenesis was observed using the methods of squash, cytolysis, and embedding of flower before anthesis, during and after anthesis. The results showed that the flower funnelled form with many calyxes, stamens and crowns. The pollen was circular, sulcus, trilate, reticulate, and spheroid. The development of microgametophyte was at the 2 nd stages with three nucleuses and the pistil developed after anthesis.  Anthesis was taken place at night time, fertilization and pollen developed before anthesis and has not germinating. A single pistil, the head of pistil with many branches, the style longer than the stamen, open type.  Seeds anathrophus , endosperm and embryo with the globular shaped, developed 5 days after anthesis, the embryo torpedo likes and the differentiation of primer tissues seen in the seeds 7 days after anthesis, and arilus generated from development of megasporangium. Keywords: embedding, self incompatibility, sferoidal, anatrophus, arillus.